Parechovirus A3 (PeV‐A3)‐associated myalgia/myositis occurs irrespective of its genetic cluster: a longitudinal molecular epidemiology of PeV‐A3 in Yamagata, Japan between 2003 and 2016. Issue 3 (March 2019) - Mizuta, Katsumi; Aoki, Yoko; Komabayashi, Kenichi; Tanaka, Shizuka; Yamakawa, Tatsushi; Shimizu, Yukitoshi; Itagaki, Tsutomu; Katsushima, Fumio; Katsushima, Yuriko; Ikeda, Tatsuya
Abstract : N/A: No longitudinal molecular epidemiology of parechovirus A3 (PeV‐A3) over a decade is available and PeV‐A3‐associated myalgia/myositis has been reported only in Japan. Thus, we aimed to clarify the longitudinal molecular epidemiology of PeV‐A3 with a major focus on the strains detected from PeV‐A3‐associated myalgia/myositis cases. We performed sequence and phylogenetic analysis for the VP1 region of PeV‐A3 strains in Yamagata, Japan, between 2003 and 2016. The phylogenetic analysis indicated that PeV‐A3 strains caused PeV‐A3‐associated myalgia/myositis as well as a variety of infectious diseases, ranging from mild to severe, in subjects ranging from neonates to adults, irrespective of genetic cluster or variations. PeV‐A3 strains are causative agents of a variety of human diseases, irrespective of their genetic cluster. Furthermore, we consider that PeV‐A3‐associated myalgia/myositis may occur, not only in Japan, but also in other countries, as closely related PeV‐A3 strains have been circulating around the world.